Extractive Metallurgy Division - Hydrogen Precipitation of Nickel from Buffered Acid Solutions - S. C. Sircar; D. R. Wiles (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1961)
The rate has been studied of the hydrogen reduction of nickel ions in acetate -buffered solutions, using a nickel catalyst. At temperatures between 130°and 160°C, the rate is found to be proportional to the catalyst area, the nickel ion concentration, and the hydrogen pressure. The effect of hydrogen ions is to reduce the observed rate, likely by causing the reverse reaction (dissolution) to proceed. The experimental activation energy was found to be 25 kcal per mole. THE precipitation of metals and lower oxides from solution by hydrogen reduction has been quite actively investigated during the past few years.1 In the case of nickel, the kinetics of the precipitation have been studied in ammonia solution2 but extension of this study to acid solutions has not attracted much interest, largely because of the unfavorable thermodynamics at all but the lowest acidities. For example, Schaufelberger foundg that only 10 pct reduction of nickel could be effected in sulphate solutions. One kinetic study of the reduction of Ni++ has been reported by Knacke, Pawlek, and Sussmuth,4 in which the order of the reaction was found to be one in nickel ion and one-half in hydrogen pressure. No mention was made as to the part played by the nickel catalyst, or by the pH of the solution. Moreover, the activation energy reported (4 .12 kcal per mole) is so low as to lead to some question as to whether diffusion might be playing a major role in determining the kinetics. We have recently completed a study5 of the kinetics of the hydrogen precipitation of nickel from acetate-buffered acidic solutions whose results confirm and amplify those of Knacke et al. EXPERIMENTAL PROCEDURES The work was done in a high-pressure autoclavee by the usual technique of removing small samples of the solution for analysis. Nickel analysis was done colorimetrically by the dimethylglyoxime method.' The catalyst used was carbonyl nickel powder (Standard A powder of the Mond Nickel Co., Ltd.) which was found to be composed of spheres of less than 350 mesh. The surface area of the powder was determined in this laboratory by the B. E. T. method to be 1.85 sq m (m2) per g. The catalyst was added to the solution only after the proper temperature and pressure had been reached. Agitation of the baffled system was by a turbine-type impeller, rotated at speeds between 400 and 750 rpm. The reduction rate was found to be independent of the stirring rate, so it was assumed that diffusion in the liquid does not limit the rate. In typical experiments, the nickel concentration was unchanged during an induction period of variable length. The concentration then decreased sharply, and gradually levelled off to approach the final equilibrium value. In some cases, notably at high stirring rates, the nickel concentration was found to increase considerably during the induction period, and then to decrease. In all cases, the rate was determined from the slope of the tangent to the rate curve as the concentration first decreased below the initial value. This is seen in Fig. 1. The rate measurements were found to be reproducible to within about 5 and to be quite independent of the nature or duration of the induction period. The range of conditions used is given in Table I.